A telescope detection system for direct and high resolution spectrometry of intense neutron fields. (February 2016) - Agosteo, S.; Fazzi, A.; Introini, M.V.; Lorenzoli, M.; Pola, A.
Abstract: A high energy- and spatial-resolution telescope detector was designed and constructed for neutron spectrometry of intense neutron fields. The detector is constituted by a plastic scintillator coupled to a monolithic silicon telescope (MST), in turn consisting of a ΔE and an E stage. The scintillator behaves as an "active" recoil-proton converter, since it measures the deposited energy of the recoil-protons generated across. The MST measures the residual energy of recoil-protons downstream of the converter and also discriminates recoil-protons from photons associated to the neutron field. The lay-out of the scintillator/MST system was optimized through an analytical model for selecting the angular range of the scattered protons. The use of unfolding techniques for reconstructing the neutron energy distribution was thus avoided with reasonable uncertainty (about 1.6% in neutron energy) and efficiency (of the order of 10 −6 counts per unit neutron fluence). A semi-empirical procedure was also developed for correcting the non-linearity in light emission from the organic scintillator. The spectrometer was characterized with quasi-monoenergetic and continuous fields of neutrons generated at the CN Van De Graaff accelerator of the INFN-Legnaro National Laboratory, Italy, showing satisfactory agreement with literature data. Highlights: An innovative neutron spectrometer based on a monolithic telescope is proposed. The device exploits an active-converter. The geometrical configuration allows to have a high resolution (<250 keV-FWHM). The system demonstrates to perform a direct measurement of neutron spectra.